Evidence-based conservative rehabilitation for posterior glenohumeral instability: A systematic review. (November 2016) - McIntyre, Kelli; Bélanger, Annie; Dhir, Jasdeep; Somerville, Lyndsay; Watson, Lyn; Willis, Myles; Sadi, Jackie
Abstract: Study design: Systematic review. Objectives: To identify the best evidenced-based approach for the conservative rehabilitation of patients with posterior glenohumeral instability. Background: Posterior glenohumeral instability is more common than previously thought. Proper management is imperative to control symptoms and maximize function. Methods: We conducted an electronic search, up to November 2014, for English-language studies involving rehabilitation of posterior shoulder instability. A manual search of reference lists of included articles and previously published reviews was also performed. Results: Five studies met the review inclusion criteria. Most studies demonstrated that rotator cuff and posterior deltoid strengthening could reduce instability recurrence and pain, and increase function, mainly in those with atraumatic posterior instability without previous surgery. These studies were mainly case series or retrospective designs. Conclusions: Rotator cuff and posterior deltoid strengthening may help with symptom-management and functioning in those with posterior glenohumeral instability. Further research is needed to detect statistically significant outcomes from conservative treatment. Level of evidence: Therapy, Level 3. Highlights: Posterior shoulder instability (PI) has historically been under-diagnosed. Activities with shoulder adduction and internal rotation pose a risk factors for PI. Rotator cuff strengthening should be initiated in patients presenting with PI. Rehabilitation must be a maintained for management of symptoms.